THE EFFECT MIND MAPPING TECHNIQUE AND VOCABULARY MASTERY ON STUDENT’S WRITING SKILL - Megawati Megawati; Yuliwati Yuliwati; Eka Rista Harimurti (STKIP Persada Khatulistiwa Sintang, 2021)
The purposes of this research is to know the effect mind mapping technique and vocabulary mastery on students’writing skill. Also how the implementation mind mapping technique on students’writing skill. Students need vocabulary mastery to arrange the sentences for getting a good paragraph and mind mapping technique is one of the technique that use to treat students for getting writing well. This research use experiments method. There were 40 students chosen at random from fourth grade semester English Education at STKIP Kusuma Negara Jakarta.Collecting data use test writing skill. Research of instrument has tested and tried by the validity and reliability test used the SPSS (Statistic Program Social Science). Data analyzed by using kolmogorv Smirov, know data was normality.The text analysis is to test the data homogeneity by using Levenu’s test, to see if the population was derived from homogeneous population. The result of this research concluded that 1) Using Mind Mapping Technique has significant effect on student’s writing skill. Result F for mind mapping (A) Fo=290.285 and sig.= 0.000<0.05, then the conclusion is that there is significant effect between mind mapping technique (X1) on student’s writing skills. 2). Vocabulary mastery gave the significant effect to the student’s writing skill. Result research F for vocabulary mastery (B) Fo=91.401 and sig.= 0.000<0.05. It has shown that there is significant effect vocabulary mastery (X2) on student’s writing skills. 3) There is significant effect interaction between mind mapping and vocabulary mastery on student’s writing skill. Result of this research F from mind mapping (A) and vocabulary (B) Fo=5.274 and sig.=0.028<0.05. Using mind mapping technique in learning give effect in students’writing skill. Students who have rich vocabulary mastery can get good writing English.Keywords: Podcasts, Promote, Speaking, Online Learning